Coffee Consumption of Istanbul City Communities in the XVI-XVIII Centuries AD - Rafsanjani, Afida Rizma Liana; Hajar, Imam Ibnu (Universitas Islam Negeri Sumatera Utara, 2025)
This research aims to describe and answer the following questions; What is the image of the people of Istanbul City in the 16th Century AD?, How did coffee shops develop in the City of Istanbul?, and what was the coffee consumption of the people of Istanbul City in the 16th-18th Century AD? To answer this question the author uses historical research methods. The historical method is carried out systematically and objectively through several stages; topic selection, heuristics, historical criticism, interpretation and historiography. The approach used is a sociological approach. This research concludes that amidst the progress of the city of Istanbul in the 16th century AD, people had many choices of activities to fill their free time. Various entertainment venues are present, the most important of which is the presence of coffee shops. In 1554 AD, the first coffee shop opened in the Tahtakale District. The ulama had issued a haram fatwa against coffee shops, but coffee shops continued to open, even the Janissaries got involved in the coffee shop business in the 18th century AD. Ottoman Turkish coffee was made by roasting, then cooling, grinding, brewing, pouring into a teapot, and serving. in the cup. What's interesting is that coffee is a part of proposal or wedding ceremonies, and coffee shops are an important place to socialize.